2020
DOI: 10.7150/jca.46414
|View full text |Cite
|
Sign up to set email alerts
|

Value of combining PET/CT and clinicopathological features in predicting EGFR mutation in Lung Adenocarcinoma with Bone Metastasis

Abstract: Purpose: Epidermal growth factor receptor (EGFR) mutation is the most common target for precision treatment in metastatic lung adenocarcinoma. We investigated the predictive role of 18 F-FDG PET/CT and clinicopathological features for EGFR mutations in lung adenocarcinoma with bone metastasis. Methods: Seventy-five lung adenocarcinoma patients with histologically confirmed bone metastasis were included. They all received EGFR status test and PET/CT before systemic treatment. The differences of maximum standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…The results of this study suggest that patients with stage IV disease according to the TNM staging guidelines have a higher mutation rate, which is inconsistent with previous research [26], but the number of cases was small, and there may have been selection bias. Finally, univariate analysis showed that the EGFR mutation rate in non-smokers was higher than that in smokers which is consistent with another study [27,28].…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study suggest that patients with stage IV disease according to the TNM staging guidelines have a higher mutation rate, which is inconsistent with previous research [26], but the number of cases was small, and there may have been selection bias. Finally, univariate analysis showed that the EGFR mutation rate in non-smokers was higher than that in smokers which is consistent with another study [27,28].…”
Section: Discussionsupporting
confidence: 90%
“…as found in a previous study [24]. Some studies have shown that smoking is an independent predictor of EGFR mutations [14], whereas others have different results [23].…”
Section: Discussionsupporting
confidence: 65%
“…The TTF-1 positivity rate of those with the EGFR mutant was higher than that of those with the wild-type, as found in a previous study [24]. Some studies have shown that smoking is an independent predictor of EGFR mutations [14], whereas others have different results [23].…”
Section: Discussionmentioning
confidence: 55%
“…Most of the EGFR mutations are measured by tumor tissue immunohistochemistry through wounded puncture or surgery. Yao et al (125) found a correlation between EGFR mutations and 18 F-fluorodeoxyglucose positron emission tomographycomputed tomography imaging, and attempted to use this non-invasive inspection as an independent predictor. It was also verified that circulating tumor DNA (ctDNA) in the plasma can be used to detect EGFR mutations in patients with NSCLC, providing information similar to that obtained from biopsies (126).…”
Section: Epidermal Growth Factor Receptor/ Kirsten Rat Sarcoma/anaplastic Lymphoma Kinase (Egfr/kras/alk) Axismentioning
confidence: 99%